Role of the C-terminal domain of the HIV-1 glycoprotein in cell-to-cell viral transmission between T lymphocytes - Emerson, Vanessa; Haller, Claudia; Pfeiffer, Tanya; Fackler, Oliver Till; Bosch, Valerie (Retrovirology, 2010)
Mutant HIV (HIV-Env-Tr712) lacking the cytoplasmic tail of the viral glycoprotein (Env-CT) exhibits a cell-type specific replication phenotype such that replicative spread occurs in some T-cell lines (referred to as permissive cells) but fails to do so in most T-cell lines or in PBMCs (referred to as non-permissive cells). We aim to gain insight on the underlying requirement for the Env-CT for viral spread in non-permissive cells.